Bmintegrin β1: A broadly expressed molecule modulates the innate immune response of Bombyx mori. (January 2021) - Li, Chongyang; Zhang, Kui; Pan, Guangzhao; Zhang, Lei; Hu, Xin; Zhao, Gaichao; Deng, Chaowei; Tan, Mengqin; Li, Changhong; Xu, Man; Su, Jingjing; Shen, Li; et al.
Abstract: Integrins are transmembrane glycoproteins that are broadly distributed in living organisms. As a heterodimer, they contain an α and a β subunit, which are reported to be associated with various physiological and pathological processes. In the present study, a 2502 bp full-length cDNA sequence of Bmintegrin β1 was obtained from the silkworm, Bombyx mori . Bmintegrin β1 belongs to the β subunit of the integrin family and contains several typical structures of integrins. Gene expression profile analysis demonstrated that Bmintegrin β1 was ubiquitously expressed in all tested tissues and organs, with the maximum expression levels in fat body and hemocytes. The immunofluorescence results showed that Bmintegrin β1 was located in the cell membrane and widely distributed in fat bodies and different types of hemocytes. Bmintegrin β1 expression was remarkably increased after challenging with different kinds of bacteria and pathogen-associated molecular patterns (PAMPs). Further investigation revealed that Bmintegrin β1 could participate in the agglutination of pathogenic bacteria possibly through direct binding with the relative bacteria and PAMPs. Altogether, this study provides a novel insight into the immune functional features of Bmintegrin β1. Highlights: The subcellular location of Bmintegrin β1 in fat body and different types of hemocytes was analyzed. Bmintegrin β1 responded to stimulation after challenging with different types of PAMPs and bacteria. Bmintegrin β1 is a broad-spectrum recognition molecule of the pathogens in silkworm.